Contractors perspective of preferred risk allocation in public-private partnership (PPP) project in Pahang - Kwai Loon, Tan (2014)
Public private partnership (PPP) procurement was introduced into Malaysia through the Ninth Malaysia Plan in March 2006. PPP capable to transfer risk away from public sector to private sector. Therefore, it is important for the public and private parties to understand the risks through the whole project lifecycle prior the risk allocation agreement is made. This study aims to identify the critical risk factors of PPP projects in Pahang and to examine the preferred risk allocations for PPP projects in Pahang. Data were collected by using a set of survey questionnaire among the contractors (one representative) in each company in Grade 7 of Construction Industry Development Board (CIDB) in Pahang. Results from the study indicated that top five risk factors in Pahang are: construction time delay”, “land acquisition”, “delay in project approvals and permits”, “design deficiency” and “inflation rate volatility”. Lastly, on risk allocation preferences, this study indicated that 7 risks out of 46 risks would be preferably allocated to the public sector while 25 risks could be assigned to private sector. 11 risks were preferred to be shared by both public and private parties and the remaining of 3 risks depended on project circumstances. The results provided sufficient insight and understanding into the process of PPP as well as look deeply into the critical risks associate in the PPP projects and the contractors’ preferred risk allocation for ensuring success of PPP projects